Review of long-term biodiversity monitoring programs (Zoological Records and Reviews, 2025)
Long-term biodiversity monitoring programs (LTBMPs) are the foundational infrastructure for detecting population trends,evaluating conservation policy effectiveness, and understanding ecosystem responses to global environmental change.Yet the global portfolio of LTBMPs is severely uneven in geographic coverage, taxonomic scope, methodologicalconsistency, and data accessibility, limiting the capacity to detect biodiversity change at scales relevant to internationalpolicy frameworks. This review synthesises evidence from 178 primary studies and programme evaluations (2000-2025)examining the design, performance, and policy relevance of LTBMPs across terrestrial, freshwater, and marineecosystems, with a focus on European monitoring infrastructure. We evaluate 24 major European and global LTBMPsacross six performance dimensions: temporal coverage, spatial replication, taxonomic breadth, methodologicalconsistency, open data provision, and policy linkage. The UK Countryside Survey and Swiss Biodiversity Monitoringprogramme achieve the highest overall performance scores (composite 2.72 and 2.68/3.0 respectively), distinguished bymulti-taxon design, consistent long-term protocols, and direct policy linkage. A critical analysis identifies five structuraldeficiencies common to European monitoring: inadequate freshwater invertebrate coverage outside WFD obligations,near-absence of soil biodiversity monitoring, insufficient taxonomic expertise to sustain morphological identificationprogrammes, geographic gaps in Southern and Eastern Europe, and funding cycle mismatches that interrupt time seriesat critical junctures. Emerging solutions -- citizen science integration, eDNA metabarcoding, automated acousticmonitoring, and open data platforms (GBIF, LTER-Europe) -- are evaluated for their capacity to address thesedeficiencies. A design framework for next-generation European biodiversity monitoring is presented.